THE RELATIONSHIP BETWEEN TREATMENT PHASE AND NUTRITIONAL STATUS IN ADULT TUBERCULOSIS PATIENTS AT PUBLIC HEALTH CENTERS IN JAMBI CITY - Wulandari, Putri Sari; Karolina, Maria Estela; Hanina; Lipinwati (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
Background: Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis. Treatment of tuberculosis consists of two phases, the intensive phase for 2 months and the continuation phase for 6-12 months. One of the factors associated with tuberculosis is nutritional status. If the patient has poor nutritional status, the risk of being infected with tuberculosis will increase. Likewise, if a patient is infected with tuberculosis, the risk of suffering from malnutrition will increase due to the side effects of taking anti-tuberculosis drugs and increased metabolism from Mycobacterium tuberculosis infection. This has a huge influence on the patient's recovery. Objective: This study aimed to investigate the relationship between treatment phase and nutritional status in adult tuberculosis patients at Public Health Centers in Jambi City. Methods: This study is an analytic type of research using a cross sectional design. This research was conducted in several Public Health Centers in Jambi City from July to October 2022. Nutritional status was assessed based on the value of Body Mass Index (BMI). The relationship between treatment phase and nutritional status was analyzed using the chi-square test. Results: The number of samples in this study were 71 patients consisting of 90.1% pulmonary TB patients and 9.9% extra pulmonary TB patients. A total of 59.2% of patients were in the intensive phase of treatment and the majority of patients had underweight nutritional status (60.6%). The results of statistical analysis obtained p value < 0.001. Conclusion: There is a relationship between treatment phase and nutritional status in adult tuberculosis patients at the Public Health Centers in Jambi City. Keywords: tuberculosis, nutritional status, treatment phase, Jambi